PENGARUH INTERAKSI SIMBOLIK TERHADAP EKSPRESI DIRI MAHASISWA: STUDI MAHASISWA ANGKATAN 2021 IAI AL-AZIS DALAM PROSES PENYELESAIAN TUGAS AKHIR: Pemaknaan Simbol, Peran Sosial, dan Pembentukan Ekspresi Diri Mahasiswa dalam Tahap Penyelesaian Skripsi - Adilah Alifia Nisa; Muhammad Nurkholis Abdurrazaq; Alfi Satria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
At the critical stage of completing the final project, academic and social pressures on students become an important context that influences the dynamics of symbolic interaction and students’ self-expression. Therefore, this study aims to understand whether symbolic interaction in interpersonal communication affects students’ self-expression during the completion of the final project. This study uses an associative quantitative approach with a survey method. Data collection was conducted through the distribution of questionnaires to 64 respondents from a total population of 179, selected based on Slovin's formula from the predetermined population. The research results show that symbolic interaction and self-expression of the 2021 class students at IAI AL-AZIS during the final project completion process occur through the use of communication symbols, both verbal and nonverbal. There is a positive and significant influence, meaning that the higher the quality of symbolic interaction, the higher the self-expression displayed by the students. This is demonstrated by the results of a simple linear regression analysis which produced a correlation coefficient (Multiple R) value of 0.8661, indicating a very strong relationship between symbolic interaction and student self-expression. The determination coefficient (R Square) value of 0.7502 indicates that the symbolic interaction variable has a 75.02% influence on student self-expression. The Adjusted R Square value of 0.7463 reinforces that this regression model is quite good and consistent. Therefore, it can be concluded that symbolic interaction has a significant and strong influence on the self-expression values of the 2021 class students at IAI AL-AZIS in completing their final project.